Glochidion ellipticum Wight extracts ameliorate dextran sulfate sodium-induced colitis in mice by modulating nuclear factor kappa-light-chain-enhancer of activated B cells signalling pathway. (8th February 2021) - Hossen, Imam; Hua, Wu; Mehmood, Arshad; Raka, Rifat Nowshin; Jingyi, Song; Jian-Ming, Jin; Min, Xu; Shakoor, Ashbala; Yanping, Cao; Wang, Chengtao; Junsong, Xiao
Abstract: Objectives: Glochidion ellipticum Wight is a medicinal plant, rich in polyphenols, frequently used by the indigenous communities of Bangladesh and possess with multiple health benefits. It exerts anti-inflammatory and antidiarrheal properties, but the detailed chemical constituents are yet to be elucidated. Methods: Glochidion ellipticum extracts were analyzed using ultra-high performance liquid chromatography/quadrupole time-of-flight mass spectrometry and then tested by both lipopolysaccharide (LPS) induced inflammation of Raw 264.7 macrophage cells and dextran sulfate sodium (DSS) induced acute colitis model. Blood serum was taken for fluorescein isothiocyanate–dextran (FITC-dextran) measurement and tissue samples were used to perform histology, RT-PCR and Western blotting. Key findings: The extracts could lower the levels of nitric oxide (NO), reactive oxygen species (ROS) and pro-inflammatory cytokines significantly in LPS induced macrophage cells. The extracts could also reduce disease activity index (DAI) score, restore antioxidants and pro-oxidants and improve macroscopic and microscopic features of colonic tissues in DSS induced mice. Expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in protein level was markedly diminished (up to 51.21% and 71.11%, respectively) in the treatment groups compared to the model group of colitic mice. Conclusions: Our findings suggested that G. ellipticum extracts ameliorate DSS colitis via blocking nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling pathway, which make them to be potential candidates for further research against inflammation and colitis.